Assisted and Opposed Mixed Convective Nanofluids Flow Over Vertical Backward Facing Step Having a Baffle - Alawi, Omer A. (American Scientific Publishers, 2015)
Laminar mixed convection flow using nanofluids over backward facing step in a heated rectangular duct having a baffle mounted on its wall are numerically simulated. The continuity, momentum and energy equations are solved using finite volume method (FVM) and the SIMPLE algorithm scheme is applied to examine the effects of the baffle on heat transfer characteristics. In this study, several parameters such as different types of nanoparticles (Al2O3, CuO, SiO2 and ZnO), different volume fractions in the range of 1% to 4%, different nanoparticles diameter in the range of 25 to 80 nm, and wall flux in the range of 10 = qw = 70 W/m2 were used. The effects of the baffle height Hb, baffle thickness Wb, and distance between the backward-facing step and baffle D on Nusselt number variation are numerically investigated. The numerical results indicate that the nanofluid with SiO2 has the highest Nusselt number compared with other nanofluids types. The Nusselt number increases as the volume fraction of nanoparticles and the Reynolds number increase, while it decreases as the nanoparticles diameter increases. Effects of baffle distances baffle heights and baffle widths on heat transfer characteristics are significant, while, effects of wall flux are slightly insignificant.